Differences in the field: economic practices and Amefricanity of Bahian Acarajé women struggling against fifa - da Silva Araujo, Larissa (Cooperativismo & Desarrollo, 2016)
Purpose: This article presents certain reflections resulting from an investigation into the dispute between Bahian Acarajé women and fifa, the governing body of world football. Description: With the hosting of the fifa World Cup in 2014, the “mega-event development model” was implemented in Brazil. This model resulted in the violation of the human rights of many Brazilians, including the Bahian Acarajé women. These women—street workers who were prevented from working in so-called “fifa exclusion zones”—resisted to have their centuries-old trade be respected as an autonomous economic activity. Viewpoint: In order to challenge the front of state-owned enterprises that was established in the country,the women engaged in various strategies of struggle spanning from negotiation to direct action. Conclusions: Based on the research findings in the field, I present some aspects of the dispute and the characteristics of the economic rationale of the Bahian Acarajé women from an intersectional and decolonial perspective.
Keywords: Amefricanity; Bahian Acarajé women; decoloniality; development; fifa; conomic rationale